Detoxifying Canavalia seeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
One of the serious problems facing most tropical developing countries is how food production can keep pace with rapidly rising populations and provide feed for livestock without resorting to expensive imports. There is a constant quest for improving...